Transient gene expression in electroporated banana (Musa spp., cv. Bluggoe, ABB group) protoplasts isolated from regenerable embryogenic cell suspensions - Sagi, L.; Remy, S.; Panis, Bartholomeus; Swennen, Rony L.; Volckaert, G. (1994)
Electroporation conditions were established for transient expression of introduced DNA in banana (Musa spp., cv. 'Bluggoe') protoplasts isolated from regenerable embryogenic cell suspensions. The following parameters were found to be highly influential: electroporation buffer, polyethylene glycol treatment and its duration before electroporation, use of a heat shock, and chimaeric gene constructs. The maximum frequency of DNA introduction as detected by an in situ assay for transient expression of the uidA gene, amounted to 1.8% of total protoplasts. Since plants have recently been regenerated from banana protoplasts at a high frequency, the present results may contribute to the production of transgenic banana.